Strategi Mengajar Dalam Meningkatkan Mutu Pembelajaran di Kelas 5 Sekolah Dasar Santo Thomas 2 Medan - Harlen Simanjuntak (LPPM Institut Nasional Laa Roiba Bogor, 2021)
The general objective of this study is to obtain an empirical description of the strategy for improving the quality of learning in grade 5 elementary schools in Medan. In particular, the objectives of this study are to, (1) find out the strategy for improving the learning quality of grade 5 elementary schools in Medan, (2) find out the results ofstrategies for improving the quality of learning for grade 5 elementary schools in Medan. Where the results of teaching strategies have not had a satisfactory impact on improving the quality of learning in schools. This is viewed from the aspect of teaching strategy, and also the results of the strategy have not given maximum effect onimproving the quality of learning at the elementary school of Santo Thomas 2 Medan.